Augmentation technologies and artificial intelligence in technical communication - Duin, Ann Hill, author.
1 online resource.
Keywords: "This book enables readers to interrogate the technical, rhetorical, theoretical, and socio-ethical challenges and opportunities involved in the development and adoption of augmentation technologies and artificial intelligence. The core of our human experience and identity is forever affected by the rise of augmentation technologies that enhance human capability or productivity. These technologies can add cognitive, physical, sensory, and emotional enhancements to the body or environment. This book demonstrates the benefits, risks, and relevance of emerging augmentation technologies such as brain-computer interaction devices for cognitive enhancement; robots marketed to improve human social interaction; wearables that extend human senses, augment creative abilities, or overcome physical limitations; implantables that amplify intelligence or memory; and devices or algorithms for emotional augmentation. It allows scholars and professionals to understand the impact of these technologies, improve digital and AI literacy and practice new methods for their design and adoption. This book will be vital reading for students, scholars and professionals in fields including technical communication, UX design, computer science, human factors, information technology, sociology of technology, and ethics. Artifacts and supplemental resources for research and teaching can be found at Link and www.routledge.com/9781138581036"--